2007
DOI: 10.1196/annals.1423.066
|View full text |Cite
|
Sign up to set email alerts
|

A New Orally Bioavailable Synthetic Androstene Inhibits Collagen‐Induced Arthritis in the Mouse

Abstract: Dehydroepiandrosterone (DHEA) has attracted much interest because of its many antiaging, metabolic and immune-modulating effects in rodents. Synthetic derivatives, such as 5-androstene-16alpha-fluoro-17-one (HE2500) and certain natural metabolites also provide benefit in various animal models of autoimmune and metabolic diseases. But, like DHEA, low potency and low oral bioavailability suggested limited usefulness of these compounds in humans. We hypothesized that HE3286, a novel 17-ethynyl derivative would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
8
32
0
Order By: Relevance
“…Treatment was associated with reductions in activated NF-B, proinflammatory cytokines mRNAs, and MMP-3. Across multiple studies, including those reported here and previously (Auci et al, 2007), we hypothesize a mechanism based on reduced NF-B activation and increased regulatory T-cell levels.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Treatment was associated with reductions in activated NF-B, proinflammatory cytokines mRNAs, and MMP-3. Across multiple studies, including those reported here and previously (Auci et al, 2007), we hypothesize a mechanism based on reduced NF-B activation and increased regulatory T-cell levels.…”
Section: Discussionsupporting
confidence: 58%
“…In our previous studies, we found that when treatment with HE3286 began at disease onset, within 13 days of treatment, HE3286-treated mice displayed a significant (p Ͻ 0.04) decrease in CIA score compared with animals treated with vehicle alone from approximately 13 days after onset to approximately 18 days after onset (Auci et al, 2007).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We also found that the mRNA and protein level of Foxp3 was decreased in the spleens of CIA rats than in normal controls and could be improved by leflunomide both in vivo and in vitro [23]. These results are consistent with our hypothesis of the involvement of CD4+CD25+Tregs in CIA progression and with the findings of several published studies, which showed an increase of CD4+CD25+Tregs in the therapeutic effect of anti-arthritic drugs on CIA [24][25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that oral treatment with HE3286 inhibited collagen-induced arthritis in the mouse (27,28). To extend and complement this finding we evaluated the effect of HE3286 in the Lewis rat model of adjuvant-induced arthritis (AIA) that represents another well known and validated preclinical model of human RA (29).…”
Section: Introductionmentioning
confidence: 96%